Mobilidades e estilos de vida de moradores e viajantes de localidades turísticas do Nordeste Brasileiro. Uma etnografia multissituada de espíritos viageiros - Lima, Rafael Cavalcante de (2023)
In contemporary life, there are many existential, psychic and social quests, which lead people to make decisions to break with their daily lives in Search of new emoticons and improvements in their lives. The Brasilian Northest Tourist Coast has been the stage for many of these lives, which are not limited to Brazilians, but to people from all over the world. International road travelers and backpackers, They are two groups of people who chose road as their home, chose the move to change their psychic and social state. The presente research takes place in Canoa Quebrada, Jericoacoara, in Ceará State, and Maragogi, Praia do Francês, in Alagoas State, tourist beaches and atronghold of people, with lifestyles guided insearch of meaning for their lives. With Tourism as a background, the work brings narratives of the lives of roadsters and backpackers, who migrated to these beaches, diásporas and mobilities, to give a dimension to their lives, in search of encounter with themselves and experiences. Therefore, this research also wants to discover the contexto of these diásporas and the ralationship they have with each other and with the social temporality experienced in recente decades. Roads, handcrafts, exchanges of empirical knowlegde, permeate the ploto f this plot. The discussion of colonial oppression, disguised as modern times, coloniality, are also importante themes addressed here. The work was carried out with na intense field experience, both past and later, allowing na ethnografic and autobiografical set, with a bold interdisciplinary cognitive discussion.